A critical review of the central role of microbial regulation in the nitrogen biogeochemical process: New insights for controlling groundwater nitrogen contamination. (15th February 2023) - Liu, Shixuan; Zheng, Tianyuan; Li, Yongxia; Zheng, Xilai
Abstract: With the increase of nitrogen (N) input in vadose zones-groundwater systems, N contamination in groundwater has become a global environmental and geological issue that has a profound impact on the ecological environment and human health. N migration in the vadose zone is the most significant means of contaminating the groundwater aquifer. However, the current research on the control of groundwater N contamination focuses solely on the content change of certain indicators and is unable to comprehend the cause and subsequent development of groundwater N contamination. These factors pose significant environmental management challenges in areas where groundwater is contaminated with nitrate. In recent years, research on the migration and transformation behavior of various N forms in vadose zones-groundwater systems has yielded some breakthroughs but also encountered some roadblocks. The biogeochemical behavior of nitrogen consists of a series of intricate chain reaction cycles (called N-cycle). The crucial role of microorganisms in the N biogeochemical process has attracted the interest of soil carbon- and N-cycle researchers and become a hot topic of study. Nonetheless, the role of microbial regulation in groundwater systems has been largely neglected and needs to be summarized immediately. Consequently, this review summarizes recent advancements, mechanisms, and challenges, and proposes a dynamic perspective on microbial regulation. On the basis of these findings, we propose a dynamic and comprehensive groundwater N system centered on microbial regulation. In addition, we critically summarized the migration and transformation behavior of the most recent N indicators, the impact of global environmental change on each N component, and the non-negligible effects of these factors on the control of groundwater N contamination. Future research must focus on the migration and transformation behavior of nitrogen in the deep vadose zone, based on the dynamic regulation of microorganisms, and complete the missing pieces of the developed N-cycle index system. These are essential for providing scientific guidance for global N management and effectively mitigating N contamination in groundwater. Graphical abstract: Image 1 Highlights: Biogeochemical processes and mechanisms of nitrogen in vadose zone are reviewed. Challenges and future direction of groundwater nitrate contamination control are discussed. Central role of microbial regulation in N-cycle is pointed out. New nitrogen indictor system and environmental responses are concluded.